PANDANGAN ISLAM TERHADAP MANUSIA, MASYARAKAT DAN PENGETAHUAN SERTA HUBUNGANNYA DENGAN PENDIDIKAN - Hanton (El-Rusyd, 2017)
The nature of the creation of man in Islamic perspective with reference to the texts of the Qur'an, is always the starting point in terms khalaqa (create) or ja'ala (make). God as the creator of this term segalanya.Kedua, mengimformasikan that humans were created on two elements of the material and immaterial. Humans come from a kind of clay, then into germ, alaqah, and mudgah so it ended up being a perfect being, but with a wide variety of life processes that he had endured. Therefore, humans must give thanks for the gifts that have been given by God Almighty. Humans evolved through a process of education. Thus, people can be referred to as homo educandum (being able students) and homo education (being educators) .From this paradigm, leading to human-eksistensian fitrawi referred to as being pedagogical, namely; God's creatures since creation has brought the potential to educate and be educated. In the view of Islam, human nature is a religious potential inborn and the potential to grow and develop. The rate of growth and development, along with the surrounding pedagogical process involving informal education, formal education and non-formal education in the community and apply to become civil society and qur'ani.